2012
DOI: 10.1021/ie301821k
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics of Liquid–Liquid Dispersion in an Advanced-Flow Reactor

Abstract: Hydrodynamics and mass transfer of immiscible liquid–liquid flows are explored in an Advanced-Flow Reactor (AFR). These systems are emerging as one of the major commercial systems for small scale continuous flow chemistry, and characterization of the transport phenomena is critical for reaction implementation. With hexane/water as a model system, we use flow visualization techniques to determine drop size distribution, hexane holdup, and specific interfacial areas for a phase flow rate range of 10–80 mL/min. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 54 publications
2
72
0
Order By: Relevance
“…Excellent mass transfer rates are also achieved in the LFR. Complete conversions are obtained within the first three hearts for all gas flow rates with the observations from Woitalka et al [15] for liquid-liquid systems, and are at least one order of magnitude larger if compared to conventional multiphase contactors [16,17].…”
Section: ∂Csupporting
confidence: 60%
See 1 more Smart Citation
“…Excellent mass transfer rates are also achieved in the LFR. Complete conversions are obtained within the first three hearts for all gas flow rates with the observations from Woitalka et al [15] for liquid-liquid systems, and are at least one order of magnitude larger if compared to conventional multiphase contactors [16,17].…”
Section: ∂Csupporting
confidence: 60%
“…Since the increase in throughput in the AFR is achieved by increasing the channel size (1 mm of minimum channel dimension) from the micron scale to the milli scale, questions arise regarding the mass transfer performance in this device. Previous mass transfer studies of the AFR with 1-butanol/ water/succinic acid [15], carbon dioxide/water [16], hexane/water [17] systems have shown that the overall mass transfer coefficients are in the range 0.1-10/s, depending on the flow rates of each phase [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…They dissipate energy continuously throughout the reactor's volume and generate a dispersion smaller in size than slugs [23][24][25]. The drawback of this approach is a generally greater pressure loss and/or lower residence time.…”
Section: Introductionmentioning
confidence: 99%
“…From the process control point of view, as well as from the production scale increase, this is beneficial as compared to the tubing system. For further scale-up of the developed process, Corning AFR™ systems should be considered as already shown in the literature for the nonenzymatic reactions [32][33][34][35]. The obtained emulsion of n-heptane droplets in an aqueous phase provided very large interfacial area for the esterification of isoamyl alcohol and acetic anhydride catalyzed by CaLB, which positions itself on the n-heptane-buffer interface.…”
Section: Resultsmentioning
confidence: 99%